N-glycan Remodeling Using Mannosidase Inhibitors to Increase High-mannose Glycans on Acid α-Glucosidase in Transgenic Rice Cell Cultures. Issue 1 (December 2018) - Choi, Hong-Yeol; Park, Heajin; Hong, Jong; Kim, Sun-Dal; Kwon, Jun-Young; You, SeungKwan; Do, Jonghye; Lee, Dong-Yup; Kim, Ha; Kim, Dong-Il
Abstract Glycoengineering of plant expression systems is a prerequisite for the production of biopharmaceuticals that are compatible with animal-derived glycoproteins. Large amounts of high-mannose glycans such as Man7 GlcNAc2, Man8 GlcNAc2, and Man9 GlcNAc2 (Man7/8/9), which can be favorably modified by chemical conjugation of mannose-6-phosphate, are desirable for lysosomal enzyme targeting. This study proposed a rice cell-based glycoengineering strategy using two different mannosidase inhibitors, kifunensine (KIF) and swainsonine (SWA), to increase Man7/8/9 glycoforms of recombinant human acid α-glucosidase (rhGAA), which is a therapeutic enzyme for Pompe disease. Response surface methodology was used to investigate the effects of the mannosidase inhibitors and to evaluate the synergistic effect of glycoengineering on rhGAA. Both inhibitors suppressed formation of plant-specific complex and paucimannose typeN -glycans. SWA increased hybrid type glycans while KIF significantly increased Man7/8/9. Interestingly, the combination of KIF and SWA more effectively enhanced synthesis of Man7/8/9, especially Man9, than KIF alone. These changes show that SWA in combination with KIF more efficiently inhibited ER α-mannosidase II, resulting in a synergistic effect on synthesis of Man7/8/9. In conclusion, combined KIF and SWA treatment in rice cell culture media can be an effective method for the production of rhGAA displaying dominantly Man7/8/9 glycoforms without genetic manipulation of glycosylation.